Challenges for Private English Tutors Teaching in Kendari - Lisa Indrajaya; Mursalim Mursalim; Aris Badara (Halu Oleo University, 2022)
The objectives of this study were to investigate the challenges faced by private English tutors in teaching and the strategies they used to deal with these challenges. This research employed a qualitative approach, using semi-structured interviews to collect data from seven private English tutors enrolled in different course institutions. Based on the participants' interviews, the study identified 15 challenges and 16 ways of dealing with them. Time management and mood consistency appeared to be common issues among the challenges faced by private English tutors, as evidenced by aspects such as student motivation, discipline, teaching procedures, materials, and the mood of both the tutors and students. To overcome these challenges, tutors struggled to become more flexible in responding to their students' needs, given their status as hired service providers who offer personalized attention to help students learn English.